Analysis of Selenoprotein F Binding to UDP‐Glucose:Glycoprotein Glucosyltransferase (UGGT) by a Photoreactive Crosslinker - Higashi, Sayaka; Imamura, Yuki; Kikuma, Takashi; Matoba, Takahiro; Orita, Saya; Yamaguchi, Yoshiki; Ito, Yukishige; Takeda, Yoichi (Chembiochem : a European journal of chemical biology, 2023)
In the endoplasmic reticulum glycoprotein quality control system, UDP‐glucose : glycoprotein glucosyltransferase (UGGT) functions as a folding sensor. Although it is known to form a heterodimer with selenoprotein F (SelenoF), the details of the complex formation remain obscure. A pulldown assay using co‐transfected SelenoF and truncated mutants of human UGGT1 (HUGT1) revealed that SelenoF binds to the TRXL2 domain of HUGT1. Additionally, a newly developed photoaffinity crosslinker was selectively introduced into cysteine residues of recombinant SelenoF to determine the spatial orientation of SelenoF to HUGT1. The crosslinking experiments showed that SelenoF formed a covalent bond with amino acids in the TRXL3 region and the interdomain between βS2 and GT24 of HUGT1 via the synthetic crosslinker. SelenoF might play a role in assessing and refining the disulfide bonds of misfolded glycoproteins in the hydrophobic cavity of HUGT1 as it binds to the highly flexible region of HUGT1 to reach its long hydrophobic cavity. Clarification of the SelenoF‐binding domain of UGGT and its relative position will help predict and reveal the function of SelenoF from a structural perspective. Selenoprotein F binds to the TRXL2 domain of human UGGT1, and it forms a covalent bond with amino acids in the TRXL3 region and the interdomain between βS2 and GT24 of human UGGT1 via a synthetic crosslinker.